2009
DOI: 10.1518/155534309x12599553478791
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concept of Team Situation Awareness in a Simulated Air Combat Environment

Abstract: This paper evaluates team SA in air combat simulations. Team composition (in terms of diversity in team members' experience) as a factor that could influence team SA is analyzed in a study of 16 military fighter pilots performing simulated air combat missions in teams of two. The study used different measures to assess team SA, including SAGAT, self-appraisal, appraisal of teammate's state, and teamwork behavior and communication. The analysis of intercorrelations between different measures of team SA shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
(66 reference statements)
3
22
1
Order By: Relevance
“…2. Overconfidence would be more pronounced on the more difficult task (Lichtenstein et al, 1982); in this case Level 3 versus Levels 1 and These data are reported, within a different theoretical context, in Sulistyawati, Wickens, and Chui (2009).…”
mentioning
confidence: 62%
“…2. Overconfidence would be more pronounced on the more difficult task (Lichtenstein et al, 1982); in this case Level 3 versus Levels 1 and These data are reported, within a different theoretical context, in Sulistyawati, Wickens, and Chui (2009).…”
mentioning
confidence: 62%
“…A number of studies reviewed here were in line with these recommendations, for example, focusing on overall over-or underconfidence in SA rather than simple correlations (Lichacz, 2008(Lichacz, , 2009Lichacz et al, 2003;Sulistyawati et al, 2009Sulistyawati et al, , 2011. Others attempted to separate response bias from sensitivity assessments using d' and ROC curves (Edgar, Edgar, & Curry, 2003;McGuinness, 2004).…”
Section: Methodological Considerationsmentioning
confidence: 78%
“…At least one measure of SA, QUASA, has attempted to combine both an objective assessment of SA (via SAGAT like probes), along with a subjective rating of how confident the person is in their answers (Edgar, Edgar, & Curry, 2003;McGuinness, 2004). Related to the issue of meta-awareness, the appropriate calibration of a person's confidence level (e.g., degree of underconfidence or overconfidence) has also received attention (Lichacz, 2008(Lichacz, , 2009Sulistyawati, Wickens, & Chui, 2009, 2011.…”
Section: Confidence In Samentioning
confidence: 99%
“…c) The Team Not all cyber defense analysts work in a team, but all personnel surveyed here indicated a team is critical to their success. Situation awareness in the team-critical environment has been the topic of study, even in the cyber domain [28]- [30]. The team dynamic brings several additional awareness requirements, uncovered in our analysis of cyber defenders.…”
Section: A) the Networkmentioning
confidence: 96%